Measurement of reverberation time using Time Delay Spectrometry (TDS) - PAPANIKOLAOU, G.; PSAROUDAKIS, V.; NISTIKAKIS, M. (Archives of Acoustics, 1993)
In the series of papers printed in the Journal of Audio Engineering Society in late sixties and early seventies, Richard C. Heyser introduced a revolutionary measurements technique which he named Time Delay Spectrometry (TDS) [1-6]. This technique allowed measurements to be conducted on systems that are inherently time-delaying, such as acoustic and electroacoustics systems, even non-linear ones, and being difficult to be maesured by means of traditional techniques, due to the time delay involved in the measurements.